Associations of lifetime traumatic experience with dysfunctional eating patterns and postsurgery weight loss in adults with obesity: A retrospective study. (30th March 2018) - Ruffault, Alexis; Vaugeois, Fanny; Barsamian, Charles; Lurbe i Puerto, Kàtia; Le Quentrec‐Creven, Gérane; Flahault, Cécile; Naudé, Anne‐Jeanne; Ferrand, Margot; Rives‐Lange, Claire; Czernichow, Sébastien; Carette, Claire
Abstract: This study aimed to examine the associations of lifetime traumatic experience with presurgery and postsurgery eating pathology and postoperative weight loss in a sample of adult bariatric surgery patients using electronic medical record (EMR) data. Presurgery lifetime exposure to traumatic event, presurgery and postsurgery dysfunctional eating patterns, and post‐operative total and excess weight losses were extracted from electronic medical records of 200 adult bariatric surgery patients in 2013 and 2014. Logistic regression analyses were conducted. During their lifetime, 60.5% of the patients (81.5% women, age = 44.4 ± 11.5 years; BMIpre = 44.9 ± 5.5 kg/m 2 ) reported that they were exposed to a traumatic event. Before surgery, trauma exposure was associated with impulsive, compulsive, or restrictive eating patterns (OR = 2.40), overeating or disturbed eating (OR = 1.55), and grazing or night eating behaviours (OR = 1.72). After surgery, trauma exposure was associated with lower total weight loss at 6 (OR = 2.06) and 24 months (OR = 2.06), and to overeating or disturbed eating (OR = 1.53) 12 months after surgery. Bariatric surgery candidates with a history of trauma exposure could benefit from closer medical, dietetic, and/or psychological follow‐up care to avoid insufficient postoperative weight loss as well as reappearance of dysfunctional eating patterns after surgery.